Employee Commitment: An Introduction and Roadmap - Meyer, John (2016)
an. introduction. and. roadmap. John. P. Meyer. Commitments are important. To wit, when politicians want to convince voters that they are serious about an issue, they make commitments. Similarly, businesses pledge their commitment to ...